2022
DOI: 10.1071/sr22119
|View full text |Cite
|
Sign up to set email alerts
|

No-till farming: prospects, challenges – productivity, soil health, and ecosystem services

Abstract: Globally, declining soil quality due to soil degradation is of great concern, and directly affects crop production, soil health and sustainability of natural resources. In conventional farming practices, the loss of fertile topsoil via runoff and erosion from arable land is a big concern. In addition, changes in land use and management practices result in loss of soil organic carbon (SOC) stock by −10–59%. The change from conventional till (CT) with residue burning/removal to no-till (NT) farming with residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Globally, the long-term no-till farming challenges crop productivity, soil health, and ecosystem services address the direct effects on crop production and soil health compared to conventional farming practices, such as the loss of fertile topsoil via runoff and erosion or declining soil quality due to soil degradation [64]. On the contrary, studies on plant pathogenic fungi show that the no-till increases significantly in topsoil the soil-borne plant pathogens, e.g., Rhizoctonia solani, as well as the frequency of others, such as Pythium spp., compared with conventional tillage [65].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the long-term no-till farming challenges crop productivity, soil health, and ecosystem services address the direct effects on crop production and soil health compared to conventional farming practices, such as the loss of fertile topsoil via runoff and erosion or declining soil quality due to soil degradation [64]. On the contrary, studies on plant pathogenic fungi show that the no-till increases significantly in topsoil the soil-borne plant pathogens, e.g., Rhizoctonia solani, as well as the frequency of others, such as Pythium spp., compared with conventional tillage [65].…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have indicated that strategic tillage can improve soil biological activity, increase nutrient availability, and enhance soil organic carbon content [22]. (ii) Weed control: tillage plays a crucial role in weed management by disrupting weed growth, burying weed seeds, and uprooting established weeds [16]. Studies have demonstrated the effectiveness of strategic tillage in suppressing weed populations and reducing weed biomass [23,24].…”
Section: Key Principles and Objectivesmentioning
confidence: 99%
“…Tillage tools are employed to bring about desired effects such as pulverization, cutting, or movement of the soil. The primary goals of strategic tillage are to enhance soil structure, control weeds, manage crop residues, improve water intake and storage, facilitate root development, and promote optimal growing conditions for crops [16].…”
Section: Introductionmentioning
confidence: 99%
“…In northern regions, glyphosate is essential for controlling perennial weeds such as Elymus repens L. Gould (couch grass) (Tørresen et al, 2003). The need for an effective E. repens control using herbicides is growing due to an increase in the extent of no‐till farming, which benefits the environment (Jayaraman & Dalal, 2022; Seitz et al, 2021). Recently, Liu et al (2021a) reported that PL adequately controlled Poa annua L. (annual bluegrass) in a growth chamber experiment.…”
Section: Introductionmentioning
confidence: 99%